Challenge in diagnosis of late onset necrotizing enterocolitis in a term infant: a case report - Gunadi, Gunadi; Sirait, D.N.; Fauzi, A.R.; Nugroho, N.; Fahri, F.; Widitjiarso, W.; Iskandar, K.; Nurnaningsih, Nurnaningsih (2021)
Background: Necrotizing enterocolitis (NEC) is a common devastating inflammatory gastrointestinal disease and frequently occurs in premature infants. Here, we reported a case of late-onset NEC in a term neonate with good outcome after surgery for long-term follow-up. Case presentation: Ten-week-old male came to emergency unit due to prolonged diarrhea and abdominal distention. He was born at gestational age of 40 weeks with birth weight and Apgar score of 2800 g and 7/8, respectively. He had no history of formula feeding. Two weeks before admitted to the hospital, the patient had frequent diarrhea with fever. He was found lethargic with abdominal distention, absence of bowel sounds and abdominal tenderness. Plain abdominal x-ray and CT scan showed gastric and intestinal dilatation and gasless colon, suggesting a small bowel obstruction, and bowel wall thickening indicating peritonitis, without any free subdiaphragmatic air (pneumoperitoneum). Moreover, the patient did not have a congenital heart disease. While in intensive medical treatment, he showed a continuous clinical deterioration. All findings were suggestive of intestinal inflammation with clinical deterioration, and we decided to perform an emergency exploratory laparotomy and found an ischemia along the jejunoileal with a perforation at 25 cm above the ileocecal valve. Subsequently, we performed a double-barrel ileostomy through a separate incision from the laparotomy. Histopathological findings confirmed the diagnosis of NEC. We closed the stoma at postoperative day 43. The patient was discharged uneventfully a month after stoma closure. Conclusion: Abdominal CT scan might be useful to establish an early recognition of late-onset NEC; thus, immediate surgical intervention might be performed to decrease its morbidity and mortality. Moreover, late-onset NEC in term neonates might occur without any risk factors or significant co-morbidities. Â© 2021, The Author(s).